Surgical stabilization of rib fractures versus nonoperative treatment in patients with multiple rib fractures following cardiopulmonary resuscitation: An international, retrospective matched case-control study. Issue 6 (24th December 2022) - Prins, Jonne T.H.; Van Lieshout, Esther M.M.; Eriksson, Evert A.; Barnes, Matthew; Blokhuis, Taco J.; Caragounis, Eva-Corina; Christie, D. Benjamin; De Loos, Erik R.; DeVoe, William B.; Formijne Jonkers, Henk A.; Kiel, Brandon; Ko, Huan-Jang; et al.
Abstract : This case-control study evaluates the effect of SSRF versus nonoperative management for multiple rib fractures after cardiopulmonary resuscitation. The SSRF group had more severe thoracic injuries with a subsequent longer ICU LOS while other outcomes were similar #SSRF #CPR #CWIS. Abstract : BACKGROUND: The presence of six or more rib fractures or a displaced rib fracture due to cardiopulmonary resuscitation (CPR) has been associated with longer hospital and intensive care unit (ICU) length of stay (LOS). Evidence on the effect of surgical stabilization of rib fractures (SSRF) following CPR is limited. This study aimed to evaluate outcomes after SSRF versus nonoperative management in patients with multiple rib fractures after CPR. METHODS: An international, retrospective study was performed in patients who underwent SSRF or nonoperative management for multiple rib fractures following CPR between January 1, 2012, and July 31, 2020. Patients who underwent SSRF were matched to nonoperative controls by cardiac arrest location and cause, rib fracture pattern, and age. The primary outcome was ICU LOS. RESULTS: Thirty-nine operatively treated patient were matched to 66 nonoperatively managed controls with comparable CPR-related characteristics. Patients who underwent SSRF more often had displaced rib fractures (n = 28 [72%] vs. n = 31 [47%]; p = 0.015) and a higher median number of displaced ribs (2 [P25 –P75, 0–3] vs. 0 [P25 –P75, 0–3]; p = 0.014). Surgical stabilization of rib fractures was performed at a median of 5 days (P25 –P75, 3–8 days) after CPR. In the nonoperative group, a rib fixation specialist was consulted in 14 patients (21%). The ICU LOS was longer in the SSRF group (13 days [P25 –P75, 9–23 days] vs. 9 days [P25 –P75, 5–15 days]; p = 0.004). Mechanical ventilator-free days, hospital LOS, thoracic complications, and mortality were similar. CONCLUSION: Despite matching, those who underwent SSRF over nonoperative management for multiple rib fractures following CPR had more severe consequential chest wall injury and a longer ICU LOS. A benefit of SSRF on in-hospital outcomes could not be demonstrated. A low consultation rate for rib fixation in the nonoperative group indicates that the consideration to perform SSRF in this population might be associated with other nonradiographic or injury-related variables. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level III. Abstract :